AABB Committee Report: reducing transfusion‐transmitted cytomegalovirus infections. Issue 6 (10th March 2016) - ,; Heddle, Nancy M.; Boeckh, Michael; Grossman, Brenda; Jacobson, Jessica; Kleinman, Steven; Tobian, Aaron A.R.; Webert, Kathryn; Wong, Edward C.C.; Roback, John D.
Abstract : Transfusion‐transmitted cytomegalovirus (TT‐CMV) is often asymptomatic, but certain patient populations, such as very low birth weight neonates, fetuses requiring intrauterine transfusion, pregnant women, patients with primary immunodeficiencies, transplant recipients, and patients receiving chemotherapy or transplantation for malignant disease, may be at risk of life‐threatening CMV infection. It is unclear whether leukoreduction of cellular blood components is sufficient to reduce TT‐CMV or whether CMV serological testing adds additional benefit to leukoreduction. The AABB CMV Prevention Work Group commissioned a systematic review to address these issues and subsequently develop clinical practice guidelines. However, the data were of poor quality, and no studies of significant size have been performed for over a decade. Rather than creating guidelines of questionable utility, the Work Group (with approval of the AABB Board of Directors) voted to prepare this Committee Report. There is wide variation in practices of using leukoreduced components alone or combining CMV‐serology and leukoreduction to prevent TT‐CMV for at‐risk patients. Other approaches may also be feasible to prevent TT‐CMV, including plasma nucleic acid testing, pathogen inactivation, and patient blood management programs to reduce the frequency of inappropriate transfusions. It is unlikely that future large‐scale clinical trials will be performed to determine whether leukoreduction, CMV‐serology, or a combination of both is superior. Consequently, alternative strategies including pragmatic randomized controlled trials, registries, and collaborations for electronic data merging, nontraditional approaches to inform evidence, or development of a systematic approach to inform expert opinion may help to address the issue of CMV‐safe blood components.